2010
DOI: 10.1631/jzus.b0900266
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative profiles of the mRNAs of ER-α and its novel variant ER-α36 in breast cancers and matched normal tissues

Abstract: Abstract:Objective: The novel estrogen receptor-α (ER-α) variant ER-α36 is reported to be functional in the estrogen signaling pathway and is related to tamoxifen resistance in breast cancer. However, ER-α36 tends to be a favorable factor for survival in patients without tamoxifen therapy. To investigate the mechanisms behind this paradox, we determined the differences between the transcriptional profiles of ER-α36 and full-length ER-α (ER-α66) in breast cancers and matched normal tissues. Methods: We analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…In this study, ER-α36 was expressed in 12 out of 14 ER-negative endometrial cancer tissues; it was expressed in 8 out of 9 cases of specific types of endometrial cancer, such as serous adenocarcinoma, which were believed to have no expression of ER. This was similar to the findings of Zheng et al [11] in breast cancer tissue samples, and no significant correlation was found in the levels of ER-α36 mRNA and ER-α66 mRNA. Our study also found that the positive expression rates of ER-α36 in endometrial cancer, atypical hyperplasia, and normal endometrium were 33, 78, and 85%, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, ER-α36 was expressed in 12 out of 14 ER-negative endometrial cancer tissues; it was expressed in 8 out of 9 cases of specific types of endometrial cancer, such as serous adenocarcinoma, which were believed to have no expression of ER. This was similar to the findings of Zheng et al [11] in breast cancer tissue samples, and no significant correlation was found in the levels of ER-α36 mRNA and ER-α66 mRNA. Our study also found that the positive expression rates of ER-α36 in endometrial cancer, atypical hyperplasia, and normal endometrium were 33, 78, and 85%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, ER-α36 expression in endometrial cancer tissues was significantly lower than in endometrial tissues, and this low level of expression was related to cervical invasion, but not to age, clinical stage, histological grade, myometrial invasion, lymph node metastasis, and pathological type. Zheng et al [11] also found in 74 patients with breast cancer that ER-α36 expression in breast cancer tissues was lower than that in normal tissues. The results showed that relatively large tumors (>2 cm), tumors with lymph nodes metastases, or advanced stage (stage III+IV) tumors had lower ER-α36 mRNA levels than those found in tissues with less advanced disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, ERα36 lacks the C-terminal activation domain of full length ERα66 and ERα46 and instead contains a unique C-terminal sequence encoded further downstream [25]. ERα36 is transcribed from a promoter located in the first intron of ERα and its expression has been observed in multiple cell and tissue types including several breast cancer cell lines and a number of different mouse tissues [25-27]. When overexpressed in HEK293 (Human Embryonic Kidney) cells or MCF7 breast cancer cells ERα36 has been shown to regulate rapid signaling pathways such as the pERK/MAPK pathway [28].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the role of ER-␣36 expression in the carcinogenesis and progression of breast cancer was unclear. Zheng et al [48] analyzed ER-␣36 messenger RNA levels in 74 paired samples of breast cancer and matched normal tissue using a PCR assay and then correlated the PCR results with the clinicopathological characteristics of these patients. Compared with the matched normal tissue, ER-␣36 mRNA levels in breast cancer tissues were lower regardless of their ERalpha66 expression status.…”
Section: Er-˛36 May Be Involved In the Carcinogenesis And Progressionmentioning
confidence: 99%